'Value statement' of BSE listed SMEs: a content analysis. (9th June 2022) - Anandan, T.R.; Gupta, Kriti Priya
We often see large organisations place a 'value statement' to express their principles, ethical codes, and beliefs to various stakeholders. Strategic scholars often advise formulating such statements for building trust and confidence. Do small business organisations also prepare value statements? Do they make it available publically? What set of values do they commonly include? What is their focus? How many core values do we generally see in such a statement? The study is about searching for answers to those unaddressed questions previously in the given context. In this study, we looked at the value statements of 39 BSE listed SMEs. We dissected the value statements using the content analysis technique and descriptive results. We also discussed their theoretical and managerial implications and future directions.